2017
DOI: 10.1063/1.5001827
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two protic ionic liquid behaviors in the presence of an electric field using molecular dynamics

Abstract: The effects of an external electric field on two ionic liquids (ILs) are investigated using molecular dynamics electrospray simulations of ethylammonium nitrate (EAN) and ethanolammonium nitrate (EOAN). In the absence of an external electric field, long alkyl chains were observed in EAN but not in EOAN. When the electric field was applied, the anions of both ILs formed a barrier along the applied field, but only in EAN did this barrier result in a static bilayer composed of two parallel layers of cations and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Addition of hydroxyl groups to terminal methyl groups in EA cations leads to a disruption of solvophobic associations between alkyl chains in EtAN, resulting in small ion aggregates, rather than a spongelike liquid morphology with extended networks. , EtAN has a less ordered liquid arrangement than that of EAN since [NO 3 ] anions are competitively coordinated with both ammonium and hydroxyl groups in EtA cations via strong HB interactions. , Generally, inclusion of additional HBs represents a source of defects in polar networks, leading to more disordered microstructures in ILs. ,,, In addition, both translational and rotational dynamics of constituent ions slow down due to the formation of HB networks in IL matrixes. When an external electric field is applied, EtAN requires a lower electric field strength than that for EAN to emit ion pairs . The applied electric field can effectively reduce the number of hydroxyl–[NO 3 ] HBs but is less effective in disrupting HBs between N–H head groups and [NO 3 ] anions.…”
Section: Pure Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of hydroxyl groups to terminal methyl groups in EA cations leads to a disruption of solvophobic associations between alkyl chains in EtAN, resulting in small ion aggregates, rather than a spongelike liquid morphology with extended networks. , EtAN has a less ordered liquid arrangement than that of EAN since [NO 3 ] anions are competitively coordinated with both ammonium and hydroxyl groups in EtA cations via strong HB interactions. , Generally, inclusion of additional HBs represents a source of defects in polar networks, leading to more disordered microstructures in ILs. ,,, In addition, both translational and rotational dynamics of constituent ions slow down due to the formation of HB networks in IL matrixes. When an external electric field is applied, EtAN requires a lower electric field strength than that for EAN to emit ion pairs . The applied electric field can effectively reduce the number of hydroxyl–[NO 3 ] HBs but is less effective in disrupting HBs between N–H head groups and [NO 3 ] anions.…”
Section: Pure Ionic Liquidsmentioning
confidence: 99%
“…When an external electric field is applied, EtAN requires a lower electric field strength than that for EAN to emit ion pairs. 331 The applied electric field can effectively reduce the number of hydroxyl−[NO 3 ] HBs but is less effective in disrupting HBs between N−H head groups and [NO 3 ] anions.…”
Section: Free Ions Ion Pairs and Ion Clustersmentioning
confidence: 99%
“…The average number of anions surrounding a cation, also known as the coordination number of EAN, was observed to be 1.9, and that of EMIM-BF 4 was 1.5, suggesting that the bulk structure of EAN is more closely packed than of EMIM-BF 4 . In other previous work [35], it was observed that EAN contains an extensive network of hydrogen bonds, which is not present in EMIM-BF 4 , possibly making the emission of ion-pairs from the EAN bulk more difficult to achieve than EMIM-BF 4 for the same extraction voltage.…”
Section: Comparison Of the Cation-anion Separation Energy Of Ean Vs mentioning
confidence: 85%
“…This explains the fundamental differences that exist in the emission characteristics of EAN and EMIM-BF 4 ILs. The extensive network of hydrogen bonds existing in EAN provides resistance to the separation of cations and anions [35]. However, it should be noted that only the normal electric field was used in these bulk simulations to separate the cation-anion pair, and the presence of both the normal and radial fields will make the emission of ions easier.…”
Section: Comparison Of the Cation-anion Separation Energy Of Ean Vs mentioning
confidence: 99%
“…1. The electrochemical properties of EAN have been analyzed in detail using both, experiments [33] and MD simulations [31,34,35]. Lenguito, et al [36] and Alonso-Matilla, et al [37] have experimentally shown that…”
Section: Figmentioning
confidence: 99%